2001
DOI: 10.1021/ma010915d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preparation Conditions on Microdomain Formation in Poly(urethane urea) Block Copolymers

Abstract: Selected poly(urethane urea) block copolymers were prepared under different conditions and their microphase-separated morphologies analyzed primarily with small-angle X-ray scattering (SAXS). Preparation conditions were varied by adjusting the temperature and vacuum pressure during solution casting. Copolymers with relatively high hard segment contents prepared under “low” vacuum conditions, where solvent is removed comparatively slowly and the copolymers spend a longer period of time in the presence of a plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 31 publications
3
68
0
1
Order By: Relevance
“…As shown in Figure 9, all of these studies demonstrated a decrease in the UTS of TPUs aged in aqueous solution at high temperatures. The percent decrease in the UTS of E2A reported in the high temperature aging study is within the range of results reported in other previous studies 18,[37][38][39] These previous high temperature aging results are in contrast with the fact that no significant hydrolytic degradation has been reported at room temperature or body temperature for any of these materials. It is interesting that all of the TPUs show a decrease in UTS independent of the soft block macrodiol used.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As shown in Figure 9, all of these studies demonstrated a decrease in the UTS of TPUs aged in aqueous solution at high temperatures. The percent decrease in the UTS of E2A reported in the high temperature aging study is within the range of results reported in other previous studies 18,[37][38][39] These previous high temperature aging results are in contrast with the fact that no significant hydrolytic degradation has been reported at room temperature or body temperature for any of these materials. It is interesting that all of the TPUs show a decrease in UTS independent of the soft block macrodiol used.…”
Section: Discussionsupporting
confidence: 88%
“…In the previous in vitro high temperature aging study, an assumption of constant water absorption with temperature was made in an attempt to predict changes in M n and tensile properties over long times at 37 C for E2A. 18 The current results show that this assumption is incorrect. Because a second key assumption was not met in the development of the TTS model, this provides yet another clue regarding the failure of the high temperature aging study to accurately predict in vivo results.…”
Section: Water Absorption Testingmentioning
confidence: 81%
See 1 more Smart Citation
“…A true understanding of these relationships, also known as structure-property relationships, is essential for optimizing composition and processing to prepare materials with predicted properties [6][7][8]. The importance of MS for controlling PU properties has been a strong motivation for developing methods to calculate the microphase composition and to characterize the DMS.…”
Section: Introductionmentioning
confidence: 99%
“…PUs are often prepared by a two-step process: formation of prepolymer (PP) with reactive NCO groups by the reaction of a low-molecular-weight polyether or polyester with an aromatic or aliphatic diisocyanate (DIC) at the first stage, which is extended with a low-molecular-weight diol or diamine (chain extender, CE) at the second stage [2,3,8,13]. The ratio PP:CE is very often chosen close to the stoichiometric 1:1, as it has been anticipated that no linear PUs are formed when the mole fraction of CE is significantly reduced [33].…”
Section: Introductionmentioning
confidence: 99%